Monitoring Vulnerabilities in the Residential Real Estate Sector in Poland - Magdalena Grothe (Gospodarka Narodowa. The Polish Journal of Economics, 2020)
This paper applies a framework for monitoring vulnerabilities in the residential real estate sector to the case of Poland. The framework considers indicators across three dimensions of real estate-related vulnerabilities, i.e. valuation, household indebtedness and the bank credit cycle, and builds a composite model-free measure shown to have a significant forecasting performance for real estate crises. The paper shows how the monitoring can be implemented for the Polish market, discusses the developments from a historical perspective, and highlights remaining data gaps.